Faktor Kecanduan Gadget Terhadap Perilaku Sosial Peserta Didik Kelas V - Sinta Nur Asiah; Budi Adjar Pranoto; Diah Sunarsih; Dedi Romli Triputra (Peneliti.net, 2022)
The era of globalization is the door to all changes, causing various developments in terms of technology. Seeing the development of technology that is increasingly messaging, brings up various consequences that can be caused by the wearer. One of the results of these technological developments is the emergence of information technology gadgets. The phenomenon of gadget addiction is currently rife in elementary school level children. This study aims to describe the factor of gadget addiction on the social behavior of fifth grade students of SD Ma'arif NU 01 Songgom in the 2022/2023 academic year. This study uses qualitative research with data collection techniques using observation, interviews and documentation. The data analysis technique used is data reduction, data presentation and conclusion drawing. This study took 19 informants consisting of students who are addicted to gadgets, fifth grade teachers, and parents of students. The results of this study indicate that: Gadget addiction factors that can affect students' social behavior are internal, situational, social, and external factors. And the impact of gadget addiction on students is a positive impact and a negative impact.